CORRELATION BETWEEN ANTIOXIDANT ACTIVITY AND SENSORY ACCEPTANCE IN HERBAL TEA BLENDS - Fitri, Zulfa Ajrina; Sunarharum, Wenny Bekti (Jurnal Teknologi Pangan, 2026)
The development of herbal tea as a functional beverage requires balancing antioxidant activity and sensory acceptance, as increasing phenolic compounds may reduce palatability. This study aimed to investigate the relationship between antioxidant properties and sensory acceptance in herbal tea blends formulated from Clitoria ternatea, Lavandula angustifolia, Cymbopogon nardus, and lemon peel. Five formulations were analyzed for total phenolic content (TPC) using the Folin–Ciocalteu method and antioxidant activity using the DPPH assay (IC₅₀). Sensory evaluation was conducted using a 7-point hedonic scale. Data were analyzed using ANOVA, Pearson correlation, and multivariate approaches, including Principal Component Analysis (PCA) and Hierarchical Cluster Analysis (HCA). Results showed that higher TPC was associated with stronger antioxidant activity, indicated by lower IC₅₀ values. The formulation with a higher proportion of Clitoria ternatea exhibited the highest TPC (5.41 mg GAE/mL) and strongest antioxidant activity (IC₅₀ 33.21 ppm), but showed lower sensory acceptance, particularly in taste and overall liking. TPC was positively correlated with antioxidant activity and color intensity, but negatively correlated with aroma, taste, and overall liking. In contrast, taste showed a very strong positive correlation with overall liking, identifying it as the primary determinant of consumer preference. Multivariate analysis revealed a clear separation between antioxidant-related variables and sensory attributes, indicating an inverse relationship between functional properties and consumer acceptance. These findings highlight the need to optimize formulations to achieve a balance between functional efficacy and sensory quality